Systematic music transcription through motion design - Nemec, Helena (2020)
Our perception is shaped by interaction and interpretation of what our senses register. This leads to overlaps in components that define the stimuli for different senses. It’s especially true for audiovisual forms, where through our life experience we create intuitive connections between characteristics of sound and appearance of its source. This project aims to exploit and systemize the phenomena of synchresis, in order to allow analysis of music in a graphic geometric form, using the audio-visual language for creating emphasis where desirable, or for composing music visually. Other than having created the system, it’s applied through motion design, owing to rhythmic value of music being time-constrained. Based on a long history of exploration in the area of Visual music, physics of sound and film-making theory, it’s undeniable that the relation exists, even if not having a single right solution.